Implementasi Reward dan Punishment Dalam Membentuk Karakter Disiplin Peserta Didik Di Madrasah Ibtidaiyah Al-Hidayah Jember - Fadilah, Siti Nur; F, Nasirudin (Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2021)
Giving stimulus from educators in the form of giving appreciation and punishment will greatly affect the way of thinking and behavior of students in achieving the goals of character education that have been set. This study aims to describe the implementation of reward and punishment in shaping the character of students' discipline. This research uses a qualitative approach with the type of case study. Methods of data collection using interviews, observation and documentation. The validity of the data used source triangulation and technical triangulation. The results of this study indicate: (1) The implementation of rewards in shaping the discipline character of students is done by giving rewards in the form of praise and giving appreciation in the form of gifts. (2) The implementation of punishment in shaping the disciplinary character of students is carried out by giving gradual warnings, giving spontaneous warnings and written warning letters. (3) Evaluation of the implementation of rewards and punishments in shaping the character of students' discipline is using process evaluation, which is an assessment carried out during the learning process by observing the attitudes of students everyday when they are in the madrasa environment.. Keywords: Reward; Punishment; Discipline; Learners Pemberian stimulus dari pendidik berupa pemberian apresiasi dan hukuman akan sangat mempengaruhi cara berpikir dan tingkah laku peserta didik dalam mencapai tujuan pendidikan karakter yang sudah ditetapkan. Penelitian ini bertujuan untuk mendeskripsikan implementasi reward dan punishment dalam membentuk karakter disiplin peserta didik. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi kasus. Metode pengumpulan data menggunakan wawancara, observasi dan dokumentasi. Keabsahan data menggunakan triangulasi sumber dan triangulasi tehnik. Hasil penelitian ini menunjukkan: (1) Implementasi reward dalam membentuk karakter kedisiplinan peserta didik dilakukan dengan memberikan reward dalam bentuk pujian serta memberikan apresiasi dalam bentuk hadiah. (2) Implementasi punishment dalam membentuk karakter kedisiplinan peserta didik dilakukan dengan cara memberi peringatan secara bertahap, memberi teguran spontan dan surat peringatan tertulis. (3) Evaluasi implementasi reward dan punishment dalam membentuk karakter kedisiplinan peserta didik adalah menggunakan evaluasi proses, yaitu penilaian yang dilakukan di saat proses pembelajaran berlangsung dengan mengamati dari sikap peserta didik sehari-hari ketika berada di lingkungan madrasah. Kata Kunci: Reward; Punishment; Disiplin; Peserta Didik